Laboratory tests to identify patients at risk of early major adverse events: a prospective pilot study. Issue 10 (October 2014) - Kaufman, M.; Bebee, B.; Bailey, J.; Robbins, R.; Hart, G. K.; Bellomo, R.
Abstract Background/Aims To test whether commonly measured laboratory variables can identify surgical patients at risk of major adverse events (death, unplanned intensive care unit (ICU) admission or rapid response team (RRT) activation). Methods We conducted a prospective observational study in a surgical ward of a university‐affiliated hospital in a cohort of 834 surgical patients admitted for >24 h. We applied a previously validated multivariable model‐derived risk assessment to each combined set of common laboratory tests to identify patients at risk. We compared the clinical course of such patients with that of control patients from the same ward who had blood tests but were identified as low risk. Results We studied 7955 batches and 73 428 individual tests in 834 patients (males 55%; average age 65.8 ± 17.6 years). Among these patients, 66 (7.9%) were identified as 'high risk'. High‐risk patients were older (75.9 vs 61.8 years of age; P < 0.0001), had much greater early (48 h) mortality (6/66 (9%) vs 4/768 (0.5%); P < 0.0001) and greater overall hospital mortality (11/66 (16.7%) vs 9/768 (1.2%); P < 0.0001). They also had more early (8/66 (12.1%) vs 14/768 (1.8%); P = 0.0001) and overall in‐hospital unplanned ICU admissions (12/66 (18.2%) vs 18/768 (2.3%); P < 0.0001) and more early (26/66 (39.3%) vs 50/768 (6.5%); P < 0.0001) and overall in‐hospital RRT calls (26/66 (39.4%) vs 55/768 (7.2%); P < 0.0001). Conclusions Commonly performed laboratory tests identify surgical ward patients at risk of early major adverse events. Further studies are needed to assess whether such identification system can be used to trigger interventions that help improve patient outcomes.